Monitoring the evolution of stiffness during ultraviolet curing of a vinyl ester resin with quasi-normal air-coupled ultrasonic spectroscopy. (December 2019) - Dominguez-Macaya, A.; Álvarez-Arenas, T.E.G.; Saenz-Dominguez, I.; Tena, I.; Aurrekoetxea, J.; Iturrospe, A.
Abstract: In this paper, quasi-normal air-coupled ultrasonic (ACUS) spectroscopy has been applied to monitor the ultraviolet (UV) curing of a vinyl ester resin. The technique is useful for measuring, with a fast single measurement, compression properties since the beginning of curing and shear properties after the gel point. Data analysis must consider the temperature variation of the system, the air and the support plate, induced by the exothermic nature of curing. Additionally, the evolution of the degree of conversion, measured with a direct current sensor, is done to estimate the variation of thickness of the resin due to the shrinkage and to correlate the mechanical properties with the curing process. Finally, the relationship between the degree of conversion and Young's modulus of a vinyl ester resin during UV curing has been successfully characterized for degrees of conversion higher than the 65%. Highlights: Characterization of the viscoelastic properties of a vinyl-ester resin during the UV cure process. Air-coupled acoustic spectroscopy with quasi-normal incidence angle to obtain longitudinal and shear viscoelastic properties. Validation of the non-contact measurements with a direct current sensor. Degree of conversion to Young's modulus relationship. Applicability for in-line manufacturing processes without possibility of direct contact between sensor and material.